The McLeod syndrome without acanthocytes - Klempíř, Jiří; Roth, Jan; Zárubová, Kateřina; Písačka, Martin; Špačková, Nataša; Tilley, Louise (Parkinsonism & related disorders, 2008)
A 45-year-old man developed chorea, behavioural changes, moderate amyotrophy and polyneuropathy. Hypertrophic cardiomyopathy and increased serum lactate dehydrogenase and creatine kinase (CK) were found. Acanthocytes were not detected. The absence of XK protein and faintly expressed Kell antigens on erythrocytes were found. Genetic test revealed a R133X mutation of the XK gene, confirming the McLeod syndrome. After 7 years he suddenly developed delirium followed by severe hypoglycaemia, hyperthermia, rhabdomyolysis, hepatic and renal failure. Malignant arrhythmia caused death.
Keywords: mutace; Hydro-Lyases; krevní skupiny - systém Kell; Chorea; transportní systémy pro neutrální aminokyseliny; Amino Acid Transport Systems, Neutral; chorea; lidé; dehydratasy; Mutation; Acanthocytes; akantocyty; Kell Blood-Group System; Male; Creatine Kinase; lidé středního věku; mužské pohlaví; Sex Chromosome Disorders; kreatinkinasa; Middle Aged; poruchy pohlavních chromozomů; Humans